El artículo 53° del decreto legislativo N° 1017, que regula el recurso administrativo de apelación en un proceso de selección, y su incidencia en los derechos constitucionales de acceso a la justicia y a un debido procedimiento - Aguilera Mendoza, María Isabel (2013)
Nowadays, public procurement has increased as growth in our country, also these processes are more complex than most processes in charge of public administration , as in these proceedings is not only involved the provision of quality and execution of works for the citizenship, but there is also a large public and private attention on the decisions made about that, one of the most important legal phenomena in public procurement are the challenges, which are resources that bring to alert an error of law or form, also the same phenomenon can limit the growth of state expressed in works and services to citizens about the Law on Public Procurement has been provided to establish a guarantee as a condition of eligibility to appeal challenge , to be described the appeal request of the bidder , however require a guarantee as access to administrative justice could limit access to administrative justice as a fundamental right of due process. Well, this legal phenomenon requires us to make an analysis and rethinking of legal matters related to this area of expertise, with our interests, matters related to procurement, for the systems to challenge in administrative and rights fundamental access of administrative justice. While public procurement is a very broad topic, but the purpose of this research is to analyze the due process as a constitutional guarantee in contracting challenges to the state, emerging as well, the need to reformulate some legal concepts, or, create new legal frameworks to ensure free access to administrative justice and to protect fish procurement for growth in our country